Counteracting greenhouse gas and aerosol influences intensify global water seasonality over the past century - Fubo Zhao; Wenbo Shi; Yiping Wu; Yanqing Lian; Qiang Li (Communications Earth & Environment)
Abstract Variations in water availability seasonality significantly impact society and ecosystems. While many studies have focused on mean or extreme precipitation, the response of water availability seasonality, influencing yearly water distribution beyond individual extremes, to human-induced climate change remains underexplored. Here we examine global and regional water availability seasonality changes from 1915 to 2014, quantifying how anthropogenic greenhouse gases and aerosols have influenced these variations using reanalysis and simulations from Coupled Model Intercomparison Project Phase 6. Despite large spatiotemporal uncertainties due to regional variability and model assumptions, we find that greenhouse gases significantly amplify the seasonality, while aerosols reduce it. Given that the positive effects of greenhouse gases surpass the aerosols’ negative effects, the counterbalancing influences have led to an overall enhancement in seasonality of water availability over the past century. This trend is expected to continue in the future as greenhouse gases-induced warming continues to rise and aerosol levels decline.